Analisis Hukum Terkait Pemanasan Global Dan Perubahan Iklim Yang Berdampak Terhadap Kelangsungan Hidup Manusia (Pembahasan Terhadap Regulasi Internasional Dan Indonesia) - Agung Maghfira Mubila; Sonya Agus Suryani; Rahmat Adip Rizki P; Lidya Aprilian Pratiwi; Ikhsan Fadillah; Elwidarifa Marwenny (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
Global warming and climate change are the biggest challenges of this century that affect human survival throughout the world. Scientific facts show that human activities, especially the burning of fossil fuels, have significantly increased the concentration of greenhouse gases in the atmosphere, causing an increase in global temperatures and extreme weather changes. The impacts of climate change are not only limited to the physical environment, such as melting ice, rising sea levels and extreme weather events, but also include social, economic, health and food security aspects. At the legislative level, many countries have adopted international regulations and agreements, such as the Paris Agreement of 2015, that limit global temperature rise to below 2 degrees Celsius. However, implementation and efforts to achieve this goal are still hotly debated among participating countries. At the societal level, climate change is causing changes in human migration patterns, increasing conflicts over natural resources and threats to global food security. These changes also impact human health through increased risks of vector-borne diseases related to climate change and the psychological impact of more frequent natural disasters. This research problem formulation includes a detailed analysis of how global warming will affect human survival from various social and economic points of view. The focus of this issue is the direct and indirect impacts of global warming on humanity, with an emphasis on empirical research and analysis of current data. The research method used is normative juridical, research that focuses on applicable legal norms or rules, and the data used is secondary. The results of the analysis show that international legal regulations related to global warming and climate change have become the main focus in efforts to mitigate negative impacts on human survival. Global warming, caused by increased emissions of greenhouse gases such as CO2, CH4, N2O, and CFCs, threatens the existence of small islands and coastal areas in Indonesia and causes sea levels to rise. Indonesia, through active participation in the Conference of the Parties (COP), has demonstrated its commitment to global efforts in addressing climate change, although challenges such as inconsistent implementation of the Kyoto Protocol and the inability to force developed countries to take responsibility for their emissions, remain has become a big problem. Efforts to mitigate and adapt to climate change at the national level, including through the National and Regional Action Plan on Greenhouse Gas Emissions (RAN/RAD GRK) as well as the Village Fund program, show proactive steps but are still faced with the challenge of coordination between institutions and resource limitations. The role of local communities and NGOs is very important in supporting the success of this policy. Overall, to achieve the goals of effective emission reduction and adaptation, synergy is needed between a stronger international legal framework, comprehensive national policies, and active participation from society and non-governmental organizations. Only with this holistic and collaborative approach can we ensure the survival of humans and the environment in the future faced with the increasingly complex challenges of climate change.